Recursos culturais e desempenho escolar: estratégias educativas e propriedades sociais de grupos familiares na zona rural de São Bernardo-MA - ALVES, Edinéia Silva (2023)
The present study investigates the relationship between cultural resources and academic performance among 9th year students at Escola Municipal Prefeito José Ferreira de Sousa, located in the rural area of the municipality of São Bernardo, eastern region of the state of Maranhão. Through the Bourdieusian concept of cultural capital, also reread by other authors, it is proposed to understand the dynamics and strategies adopted by six family groups in the process of educating their children. The problematization of this research is guided by the following question: What are the relationships between economic, social and cultural resources and the academic performance of students in the 9th year of elementary school at a school in the rural area of the municipality of São Bernardo, in the eastern region of Maranhão? The research is based on the following objectives: to analyze the relationships between economic, social and cultural resources and the academic performance of students in the 9th year of elementary school at Escola Municipal Prefeito José Ferreira de Sousa; identify the economic, social and cultural resources recruited by students' families in the schooling process; investigate the family schooling strategies adopted and how they are structured; verify how family groups perceive the educational process and the importance given to it for the formative process of their children. As a methodological procedure, participant observation and in-depth interviews were used, which are effective instruments in constructing data for analyzing the cultural, economic and social variables that make up and drive academic performance among students from popular circles who are the target of this research. For the development of the analysis, the theoretical research corpus is composed of Bourdieu (1998, 2007 and 2014), Lahire (1997), Nogueira (2004, 2013), Setton (2005), Nogueira; Almeida; Queiroz (2010), Sato (2012) and Pereira (2005). To address the dynamics and strategies mobilized by family groups in the children's schooling process, studies by Nogueira (2011), Zago (2000), Costa et al. (2013) and Souza & Silva (2003) who analyze how family educational practices have been essential to understand, more deeply, the influence generated by the work of parental monitoring of their children's school life, bringing elements that make it possible to understand how they are constructed ( consciously and unconsciously) school strategies in everyday family life in popular circles. Therefore, we realized that the development of this research made it possible to take a first look at the relationships between economic, social and cultural resources and the academic performance of students in the 9th year of elementary school at a school in the village of Currais, a rural area in the municipality of São Bernardo. of Maranhão, in the eastern region of Maranhão. In addition to knowing the factors that condition the academic performance of these students, as well as the strategies that are recruited by family groups of students from popular circles in Bernardo.